Scoping review and international multi-centre cohort study investigating teaching, knowledge and beliefs regarding physical activity as a health intervention among medical students : a comparison between Singapore and the UK - Chew, Edwin Jun Chen (2020)
Introduction: Physical inactivity is a global challenge and physicians must promote physical activity (PA) among their patients. Nevertheless, PA counselling remains inadequate due to limitations in knowledge, education and information availability. This study evaluates the understanding of PA as a health intervention and knowledge of World Health Organization (WHO) guidelines among Singapore and United Kingdom (UK) medical students, the next generation of physicians. Methods: Students from Singapore (Yong Loo Lin School of Medicine and Lee Kong Chian School of Medicine) and the UK (Universities of Cardiff, Leicester, Oxford and Birmingham) were invited to complete a 12-item online survey. Questions assessed knowledge of WHO guidelines, understanding of PA in health and illness, personal PA levels and exposure to PA counselling in clinical practice. Results: Among 633 Singapore and UK students who completed the questionnaire, 94.8% believed that PA was important in preventing disease, but only 70.9% recognised its importance in treating disease. The majority (85.3%) indicated participation in PA and exercise. General understanding of WHO guidelines for adults was poor, with less than half (46.8%) correctly answering this section. 3 (0.5%) students identified that PA in adults could be accumulated in multiple ways. Understanding of PA in health and familiarity with guidelines did not differ significantly between Singapore and UK students. Conclusion: There is considerable room for improvement in the knowledge of WHO guidelines and the role of PA in health. Education should begin during the undergraduate phase so that future doctors are better equipped to counsel their patients.